Multi-Smart and Scalable Bioligands-Free Nanomedical Platform for Intratumorally Targeted Tambjamine Delivery, a Difficult to Administrate Highly Cytotoxic Drug - Marta Pérez-Hernández; Cristina Cuscó; Cristina Benítez-García; Joaquin Bonelli; Marina Nuevo-Fonoll; Aroa Soriano; David Martínez-García; Alain Arias-Betancur; María García-Valverde; Miguel F. Segura; Roberto Quesada; Josep Rocas; et al. (Biomedicines, 2021)
Cancer is one of the leading causes of mortality worldwide due, in part, to limited success of some current therapeutic approaches. The clinical potential of many promising drugs is restricted by their systemic toxicity and lack of selectivity towards cancer cells, leading to insufficient drug concentration at the tumor site. To overcome these hurdles, we developed a novel drug delivery system based on polyurea/polyurethane nanocapsules (NCs) showing pH-synchronized amphoteric properties that facilitate their accumulation and selectivity into acidic tissues, such as tumor microenvironment. We have demonstrated that the anticancer drug used in this study, a hydrophobic anionophore named T21, increases its cytotoxic activity in acidic conditions when nanoencapsulated, which correlates with a more efficient cellular internalization. A biodistribution assay performed in mice has shown that the NCs are able to reach the tumor and the observed systemic toxicity of the free drug is significantly reduced in vivo when nanoencapsulated. Additionally, T21 antitumor activity is preserved, accompanied by tumor mass reduction compared to control mice. Altogether, this work shows these NCs as a potential drug delivery system able to reach the tumor microenvironment, reducing the undesired systemic toxic effects. Moreover, these nanosystems are prepared under scalable methodologies and straightforward process, and provide tumor selectivity through a smart mechanism independent of targeting ligands.